Respostas
respondido por:
1
Resposta:
S = { 5, 4 }
Explicação passo-a-passo:
x - y = 1
x + y = 9
------------
2x / = 10
2x = 10
x = 10/2
x = 5
x - y = 1
5 - y = 1
- y = 1 - 5
- y = - 4(-1)
y = 4
Verificando na 1° Equação
x + y = 9
5 + 4 = 9
9 = 9
lazinho732:
Obrigado mn
respondido por:
0
resolução!
x - y = 1
x + y = 9
2x = 10
x = 10/2
x = 5
y = 9 - x
y = 9 - 5
y = 4
S = { x = 5 e y = 4 }
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás